Agents Network´s and Innovation in Traditional Small Business - Barboza, Ricardo Augusto Bonotto (2016)
The universe of micro and small enterprises (MSEs) which is operating in traditional sectors of the economy have peculiar characteristics that is materialized in barriers to innovation, public policy of interventions are needed to minimize their difficulties. This study aimed to report the virtues , the limitations and difficulties of the implementation of two instruments as potential or as an actual innovations inducers in micro and small enterprises ( MSEs ) traditional base. The methodological strategy used included a qualitative research, exploratory, designed as simple cases study , with data collected through interviews and participant observation. It was found that the micro and small business traditional base, even those who are targets of public policies and programs have many difficulties to operationalize innovation. It was also noted that the junction of the two instruments potentiated innovative activities.